KESENIAN KUDA LUMPING SEBAGAI MEDIA PEMBELAJARAN PNF (STUDI KASUS KELOMPOK NGUDI BUDOYO) DI KABUPATEN BENGKULU UTARA - Hangga Pratomo; Parlan Parlan; Wahiruddin Wadin (Jurnal Pendidikan Sepanjang Hayat, 2019)
The purpose of this study was to find out the Lumping Horse Art as a Learning Media for PNF (Case Study of the Ngudi Budoyo Group) in North Bengkulu Regency. The method used is qualitative with data collection techniques, namely interviews, observation and documentation. The subject of the research is the lumping horse management board, consisting of the Chairperson, Secretary, Treasurer and Members. To prove the validity of the data, data checking was done using source, technique and time triangulation. Data were analyzed through three stages, namely, data reduction, presentation and conclusion drawing. From the results of the study it was found that the first implementation of Kuda Lumping Art was always in line with what was expected because the group always held meetings before implementation. Both learning, Kuda Lumping Art has many types of learning applications. The three factors supporting and inhibiting the implementation of Kuda Lumping are carried out with the group and the community itself in the supporting factor is the intention and enthusiasm of the community while the inhibiting factors can be caused due to lack of learning motivation, motivation and desire of the community.  Keywords: Learning Horse Lumping Arts, Entrepreneurship